2016
DOI: 10.1108/imefm-08-2015-0092
|View full text |Cite
|
Sign up to set email alerts
|

Modelling public behavioral intention to adopt Islamic banking in Uganda

Abstract: Purpose Islamic banking (IB) has resulted in abundant cross-border financial flows and diversified economic inter-linkages with over US$2tn in assets that have extended beyond Muslim countries to more established global financial centres and other emerging economies. Despite this remarkable diffusion, numerous developing and least-developed countries are yet to embrace IB. This study aims to examine the factors that determine public intention to adopt IB in Uganda. Design/methodology/approach This study unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 16 publications
8
77
3
2
Order By: Relevance
“…The findings of this study are consistent with the findings of previous researchers; for example, Lujja et al (2016a), who found a positive relationship between attitude and behavioral intention to adopt Islamic banking. Similarly, Kaawaase and Nalukwago (2017) found that attitude is a significant predictor of patronizing Islamic banking in Uganda using existing bank account holders as respondents.…”
Section: Ijif 112supporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study are consistent with the findings of previous researchers; for example, Lujja et al (2016a), who found a positive relationship between attitude and behavioral intention to adopt Islamic banking. Similarly, Kaawaase and Nalukwago (2017) found that attitude is a significant predictor of patronizing Islamic banking in Uganda using existing bank account holders as respondents.…”
Section: Ijif 112supporting
confidence: 92%
“…Previous studies on adoption of Islamic banking using evidence from Uganda suggest a number of determinants of adoption of Islamic banking (Lujja et al, 2016a;Lujja et al, 2016b;Kaawaase and Nalukwago, 2017;Lujja et al, 2018;Bananuka et al, 2019). In their study of modeling public behavioral intention to adopt Islamic banking in Uganda using the theory of reasoned action, Lujja et al (2016a) found that attitude influences behavioral intention to adopt Islamic banking in Uganda. The authors further found that subjective norm is not a significant predictor of behavioral intention to adopt Islamic banking but rather influences attitude toward the adoption of Islamic banking in Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…Various authors studied the subjective norm on adopting banking and found it the most important factor in shaping the intention of people (Gumel et al 2015;Hanudin et al, 2014;Abduh et al, 2011). Lujja et al (2016) on the contrary found that the referent group has no significant influence on shaping the intention to adopt banking. Lajuni et al (2017) suggested that a person will perform a behavior as expected by the social group under the pressure of the same even he may not be in favor of doing the action.…”
Section: Literature Reviewmentioning
confidence: 89%
“…In a study conducted in Uganda by [18], the researchers looked to determine the behavioural intention to adopt Islamic banking using TRA as the framework. The authors chose to use structural equation modelling to determine the relationship between attitude, subjective norms and public intention to adopt Islamic banking.…”
Section: Literature Reviewmentioning
confidence: 99%